HUBUNGAN EMOTIONAL EATING, POLA MAKAN, DAN AKTIVITAS FISIK DENGAN KEJADIAN OBESITAS PADA PETUGAS PUSKESMAS WILAYAH KECAMATAN MANYAR KABUPATEN GRESIK - Arin Widi Kustantri; Dwi Faqihatus Syarifah Has; Ernawati Ernawati (Ghidza Media Jurnal, 2021)
Objective: This study was to determine the relationship between emotional eating, eating patterns, and physical activity with the incidence of obesity in public health center officers in Manyar District, Gresik Regency. Methods: This was an analytic observational study with cross sectional design. Thirty six respondents were selected by purposive sampling technique. Respondent identity data, emotional eating, eating patterns, and physical activity were taken through interviews with a questionnaire guide (DEBQ-13, FFQ, and PAL). Anthropometric data were obtained through direct measurements. Statistical analysis was performed bivariate with chi square test and multivariate with multiple linear regression test. Result: This study shows the prevalence of obesity in public health center officers in Manyar District Gresik Regency of 32%. There is a relationship between emotional eating and obesity (p value 0.007 <0.05), there is no relationship between diet and obesity (p value 0.31> 0.05), and there is no relationship between physical activity and obesity (p value 0.29> 0.05). Emotional eating factor has a moderate, not so strong relationship with the incidence of obesity in public health centers in Manyar District, Gresik Regency, that is 48.2%. Conclusions: There is a relationship of emotional eating that is not so strong with the incidence of obesity, there is no relationship between diet and physical activity with obesity. Education information on Balanced Nutrition Guidelines (PGS) very much needed as a source of information to the community, especially for public health center officers in the Manyar District, Gresik Regency. Keywords: Emotional eating, Eating Patterns, Obesity, Physical Activity